Invasive polychaete Boccardia proboscidea Hartman, 1940 (Polychaeta: Spionidae) in sewage-impacted areas of the SW Atlantic coasts: morphological and reproductive patterns - Jaubet, Maria Lourdes (2014)
Boccardia proboscidea is an alien polychaete species that has been introduced to the Southwestern Atlantic Ocean. This polychaete species has invaded intertidal benthic rocky shores, and builds reefs formed by thousands of individuals per square meter with densities up to 1,500,000 ind.·m−2 in organically impacted sites. This phenomenon was first recorded in Argentina in 2008. This is the first comprehensive study on the morphology, habitat and reproductive biology of B. proboscidea associated with the sewage-induced abrasion platforms on the Argentinean coasts. Adult morphology of B. proboscidea from Mar del Plata is described and a comparison with material from other locations is made. Results showed that B. proboscidea from Mar del Plata, Argentina share the same diagnostic features as those of the individuals from the original description (California). Moreover, the results also indicated that the reproduction of this species involves a poecilogonous development (production of more than one type of offspring with both kinds of larvae) and implicates adelphophagy (nurse egg ingestion). Patterns of larval development varied both within a single brood and among broods of different females. Continuous reproduction of B. proboscidea coupled with a continuous supply of organic matter could explain the possible mechanism that led to the development of reefs.